Cardiovascular and psychopathological factors among non-sexually compulsive, sexually compulsive, and hypersexual individuals in Sao Paulo, Brazil. Issue 1 (2nd January 2020) - D. T. Scanavino, Marco; Ventuneac, Ana; Caramelli, Bruno; Naufal, Lucas; S. D. Santos Filho, Carlos; Nisida, Isabelle V. V.; Amaral, Maria L. S.; Vieira, Julie C.; Parsons, Jeffrey T.
ABSTRACT: We decided to explore the frequency of cardiovascular risk factors, according to three levels of severity of compulsive sexual behavior (CSB), namely, non-sexually compulsive (1), sexually compulsive (2), and sexually compulsive, and hypersexual (3). We also investigated the impact of a psychiatric co-morbidity on the Framingham heart risk score (FRS). 94 non-sexually compulsive, 57 sexually compulsive, and 60 hypersexual individuals underwent psychiatric interview, blood collection, self-responsiveness, and anthropometric measurement. The analyses were repeated with individuals aged up to 44 and aged more than 44 years old. Regarding the total sample, we observed significant association among those sexually compulsive, and hypersexual participants with presenting the HIV serologic status, and a greater proportion of psychiatric conditions as much as the severity of CSB increases. Individuals with substance-related disorder predicted higher Framingham scores. The analyses with people aged more than 44 years old presented some different results, such as association among presenting low FRS and the sexually compulsive participants, and sexual compulsivity predicted lower scores of the Framingham. The study points out to the relevance of comprehensive psychiatric examination of whom presenting CSB and opens an avenue forward investigation of the effect of high rates of sexual activity on cardiovascular risk.